2018
DOI: 10.1049/iet-nbt.2018.5069
|View full text |Cite
|
Sign up to set email alerts
|

Silvernanoparticles biosynthesisedusingCentella asiaticaleaf extract: apoptosis induction in MCF‐7 breast cancer cell line

Abstract: The aim of this study was to green synthesised silver nanoparticles (AgNPs) using leaf extract and investigate the cytotoxic and apoptosis-inducing effects of these nanoparticles in MCF-7 breast cancer cell line. The characteristics and morphology of the green synthesised AgNPs were evaluated using transmission electron microscopy, scanning electron microscopy, UV-visible spectroscopy, X-ray diffraction, and Fourier-transform infrared spectroscopy. The MTT assay was used to investigate the anti-proliferative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The cytotoxicity of AgNPs against MCF-7 cells was also reported in several articles. 1 , 41 , 44 , 48 , 51 , 52 , 54 However, the long-term effect of Ag/AgCl-NPs on MCF-7 cell line was not reported. In the present study, the colony of MCF-7 cells was not observed in the synthesized Ag/AgCl-NP-treated wells after two weeks as compared with the non-treated wells.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of AgNPs against MCF-7 cells was also reported in several articles. 1 , 41 , 44 , 48 , 51 , 52 , 54 However, the long-term effect of Ag/AgCl-NPs on MCF-7 cell line was not reported. In the present study, the colony of MCF-7 cells was not observed in the synthesized Ag/AgCl-NP-treated wells after two weeks as compared with the non-treated wells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies found that asiatic acid improved the developmental ability of early embryos in pigs; the main underlying mechanism was amelioration of oxidative stress and downregulation of the expression of apoptosis-related genes (Qi et al, 2020). The potential therapeutic value of C. asiatica for breast cancer mainly reflected in the promotion of apoptosis of breast cancer cells (Fard et al, 2018).…”
Section: Effects On Gynecological Diseasesmentioning
confidence: 99%
“…The total phenol content and avonoid content of C.subradiata aqueous extract and AgNPs green synthesized using the same extract were evaluated by different spectroscopic methods. Different concentrations of the lichen extract (20,40,60, 80 and 100 µg/mL) and AgNPs (2, 4, 6, 8 and 10 µg/mL) were used to perform the analysis. The TPC in the samples were determined using Folin-ciocalteau method [36] and TFC was determined using Aluminium chloride method [37].…”
Section: Determination Of Total Phenol Content (Tpc) and Total Avonoid Content (Tfc)mentioning
confidence: 99%
“…The antioxidant activity of C. subradiata extract and AgNPs were determined using different in-vitro assays. Different concentrations of C. subradiata extract (20,40,60, 80 and 100 µg/mL) and AgNPs (2, 4, 6, 8 and 10 µg/mL) were used. 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay was performed by adding 2 ml of DPPH solution in methanol to the aliquots of the samples.…”
Section: In-vitro Antioxidant Activity Of C Subradiata Extract and Agnpsmentioning
confidence: 99%
See 1 more Smart Citation